Surgery-first approach in orthognathic surgery: psychological and biological aspects - a prospective cohort study - Zingler, Sebastian; Hakim, Emad; Finke, Dominic; Brunner, Monika; Saure, Daniel; Hoffmann, Jürgen; Lux, Christopher J.; Erber, Ralf; Seeberger, Robin (Journal of cranio-maxillofacial surgery, 2017)
Introduction - The aim of this pilot study was to investigate psychological and biological changes after application of a surgery-first orthognathic treatment approach. - Methods - A prospective cohort study of 9 patients (6 women and 3 men; mean age 26.7 years) suffering from skeletal Class II and III deformities was conducted. Skeletal changes from pre-to post-treatment were analyzed based on data acquired by use of cone-beam computed tomography (CBCT). Psychological changes were analyzed using the orthognathic quality of life (OQLQ) questionnaire, Sense of Coherence 29-item scale (SOC-29) and longitudinal day-to-day questionnaire. For biological evaluation, concentrations of IL-1 β, IL-6, TGF β 1-3, MMP-2 and VEGF were assessed in crevicular fluid by bead-based multiplex assays at one preoperative and various postoperative time points. - Results - A significant improvement (P = 0.015) in quality of life, as measured with the OQLQ, was observed between baseline and 3 months post-surgery. The most affected dimensions were: facial aesthetics (p = 0.022), oral function (p = 0.051) and social aspects (p = 0.057). Sense of coherence (SOC) significantly improved after treatment by 9 points (P = 0.029). Despite the significant improvement in OQLQ and SOC during the course of the study, the personal experience of appearance varied distinctly in course and intensity. In accordance with the temporal pattern of fracture healing, the analysis of crevicular fluid revealed an increase in pro-resorptive factors (IL-1 β, IL-6 and MMP-2) at early postoperative time points, while remodeling factors (members of the TGF-β superfamily) were detected at later postoperative time points. - Conclusions - Orthognathic treatment using the surgery-first approach has a positive impact on patient's psychosocial status. Accelerated tooth movement after surgery might, to a certain extent, be due to elevated levels of bone remodeling factors with overlapping functions during fracture healing and tooth movement.
Gesehen am 21.08.2018